Genetic Selection of Peptide Aptamers That Interact and Inhibit Both Small Protein B and Alternative Ribosome-Rescue Factor A of Aeromonas veronii C4 - Liu, Peng; Chen, Yong; Wang, Dan; Tang, Yanqiong; Tang, Hongqian; Song, Haichao; Sun, Qun; Zhang, Yueling; Liu, Zhu (Frontiers in Microbiology, 2016)
Aeromonas veronii is a pathogenic gram-negative bacterium, which infects a variety of animals and results in mass mortality. The stalled-ribosome rescues are reported to ensure viability and virulence under stress conditions, of which primarily include trans-translation and alternative ribosome-rescue factor A (ArfA) in A. veronii. For identification of specific peptides that interact and inhibit the stalled-ribosome rescues, peptide aptamer library (pTRG-SN-peptides) was constructed using pTRG as vector and Staphylococcus aureus nuclease (SN) as scaffold protein, in which 16 random amino acids were introduced to form an exposed surface loop. In the meantime both Small Protein B (SmpB) which acts as one of the key components in trans-translation, and ArfA were inserted to pBT to constitute pBT-SmpB and pBT-ArfA, respectively. The peptide aptamer PA-2 was selected from pTRG-SN-peptides by bacterial two-hybrid system (B2H) employing pBT-SmpB or pBT-ArfA as baits. The conserved sites G133K134 and D138K139R140 of C-terminal SmpB were identified by interacting with N-terminal SN, and concurrently the residue K62 of ArfA was recognized by interacting with the surface loop of the specific peptide aptamer PA-2. The expression plasmids pN-SN or pN-PA-2, which combined the duplication origin of pRE112 with the neokanamycin promoter expressing SN or PA-2, were created and transformed into A. veronii C4, separately. The engineered A. veronii C4 which endowing SN or PA-2 expression impaired growth capabilities under stress conditions including temperatures, sucrose, glucose, potassium chloride (KCl) and antibiotics, and the stress-related genes rpoS and nhaP were down-regulated significantly by Quantitative Real-time PCR (qRT-PCR) when treating in 2.0% KCl. Thus, the engineered A. veronii C4 conferring PA-2 expression might be potentially attenuated vaccine, and also the peptide aptamer PA-2 could develop as anti-microbial drugs targeted to the ribosome rescued factors in A. veronii.